Constraining the Uplift History of the Transantarctic Mountains with Apatite Fission Tracks - Fisher, Teo; Bauer, Nick (ScholarWorks@CWU, 2015)
The Transantarctic Mountains (TAM) span approximately 3,000 km and stand 3 to 4 km high but their origin is not well understood. There are several competing theories regarding the origin of the TAM. One theory, rift flank uplift, involves one side of a fault rising and being eroded. Another theory, plateau collapse, involves the rifting (pulling apart) and collapse of a plateau with a remnant margin forming the TAM. The exhumation (uplift and erosion) history of the TAM is recorded in the mineral apatite. Apatite fission track (AFT) data allows us to see the duration and rate of exhumation starting at a depth of about 4 km below the surface. Decades of work in the TAM by researchers has produced an abundance of AFT data. In this study, AFT data in the TAM were compiled and plotted in ArcGIS along with geological maps and digital elevation models for analysis. The AFT data were analyzed in fault blocks segmented by major faults perpendicular to the coast. AFT data of the TAM were plotted with elevation and distance from the coastline of the Ross Sea and Ross Ice Shelf to evaluate the overall trend of each fault block in relation to the coastline. Preliminary results show more exhumation near the coastline which decreases inland and with elevation, and appears to accommodate the plateau collapse model.